Photoconductive properties of lead iodide films prepared by electron beam evaporation - 朱兴华 杨定宇 魏昭荣 孙辉 王治国 祖小涛 (Journal of semiconductors, 2010)
Lead iodide（PbI_2） films have been prepared by the electron beam evaporation technique,and their photoconductive response to visible light was investigated under different deposition and illumination conditions.It is found that the films＇ photoconductive response speed increases and the relative sensitivity decreases with the increase of substrate temperature due to the opposite requests for photo-carrier lifetime.Further,appropriately increasing the film＇s thickness and rising substrate temperature simultaneously can effectively balance the opposite demands.Under optimized conditions of a substrate temperature of 200℃,a source-substrate distance of 30 cm and a deposition time of 10 min,the prepared films exhibit the best response properties.In addition,the response to illumination with different wavelengths was also measured,revealing that the decline of response performance with increasing wavelength is due to the lower photon energy of incident light.